2021
DOI: 10.1039/d1sc00573a
|View full text |Cite
|
Sign up to set email alerts
|

Rational incorporation of defects within metal–organic frameworks generates highly active electrocatalytic sites

Abstract: The allure of metal-organic frameworks (MOFs) in heterogeneous electrocatalysis is that catalytically active sites may be designed a priori with an unparalleled degree of control. An emerging strategy to generate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 74 publications
1
42
0
Order By: Relevance
“…The Raman spectra recorded with the presence of HMF exhibit a similar result. Based on the above results and previous achievements made by Wang's and Kornienko's groups, [35, 44] we propose that the HMFOR over Ru 1 ‐NiO is dominated by the OH*‐participated oxidation pathway, instead of the E−C mechanism.…”
Section: Resultssupporting
confidence: 68%
“…The Raman spectra recorded with the presence of HMF exhibit a similar result. Based on the above results and previous achievements made by Wang's and Kornienko's groups, [35, 44] we propose that the HMFOR over Ru 1 ‐NiO is dominated by the OH*‐participated oxidation pathway, instead of the E−C mechanism.…”
Section: Resultssupporting
confidence: 68%
“…[ 36 ] For example, Kornienko's group synthesized a defective metal–organic framework (MOF) by incorporating a fraction of 2‐hydroxyterephthalic acid to replace original 2,5‐dihydroxyterephthalic acid in Ni‐MOF‐74. [ 37 ] The defective MOF (named Ni‐MOF‐74D) features 4‐coordinate NiO 4 sites in comparison with the NiO 5 sites in Ni‐MOF‐74, as shown in the Figure 3h,i. Compared with the original Ni‐MOF‐74, the defective Ni‐MOF‐74D presents increased performance for the HMF oxidation with 95% yield and 80% FE to FDCA via the DFF pathway in the presence of 10 m m HMF at pH = 12.…”
Section: Oxidative Refining Of Biomassmentioning
confidence: 99%
“…[252] Similar enhancement was also observed in Ni 2 (OH) 2 (BDC), [Co 3 (C 4 O 4 ) 2 (OH) 2 ]•3H 2 O, and Ni-MOF-74 with vacancies. [253][254][255] Li, Liu, and co-workers demonstrated that by introducing carboxyferrocene to linker vacancies in CoBDC, its OER activity is facilitated. [256]…”
Section: Chemical Conversion At the Vacancy Sitesmentioning
confidence: 99%